What Are the Applications of AI in Sports Medicine? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Artificial intelligence (AI) is rapidly transforming various fields, and sports medicine is no exception. From injury diagnosis and treatment to performance ...
Keywords: AI in Rehabilitation Medicine; Applications; Sports; Medicine; Artificial Intelligence; Machine Learning; Deep Learning